2023
DOI: 10.2166/wpt.2023.117
|View full text |Cite
|
Sign up to set email alerts
|

Coefficients and curves of hourly and daily variations of water demand for improved operation of potable water distribution systems: a case study of Chihuahua City, Mexico

Eduardo Hernandez-Samaniego,
Carmen Navarro-Gomez,
David Humberto Sánchez
et al.

Abstract: Maintaining a constant flow in a potable water distribution hydraulic system is challenging due to fluctuations caused by changes in user demand and seasonal factors. This study aimed to calculate the coefficients and curves of hourly and daily variations of water demand in the water distribution system of Chihuahua. It is crucial to understand the hydraulic system's behavior during peak demands and assess its capacity. The methodology involved calculating coefficients and curves of variation of demand based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Research conducted in Chihuahua City, Mexico, showed HPC changes from 0.07 to 1.64 [20]. Research conducted in Cracow, Poland, showed a maximum post-winter HPC of 1.77 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Chihuahua City, Mexico, showed HPC changes from 0.07 to 1.64 [20]. Research conducted in Cracow, Poland, showed a maximum post-winter HPC of 1.77 [21].…”
Section: Introductionmentioning
confidence: 99%